A process for preparing efficient adsorbent using sludge / iron tailings to recover phosphorus

Through the collaborative treatment of iron tailings and sludge, iron-modified hydrothermal carbon is prepared, and the high nitrogen-containing liquid phase product is converted into struvite fertilizer, which solves the problem of liquid phase product processing in the sludge hydrothermal carbonization process and achieves Efficient use of resources and simplification of processes.

CN118831562BInactive Publication Date: 2025-01-21NANJING INST OF ENVIRONMENTAL SCI MINIST OF ECOLOGY & ENVIRONMENT OF THE PEOPLES REPUBLIC OF CHINA
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411132995.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-19
Publication Date
2025-01-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The high nitrogen-containing liquid phase products generated by the prior art during the hydrothermal carbonization of sludge are difficult to handle, and the process is complex and resource waste is large.

Method used

Modify water and hot charcoal through iron tail mine, muddy impretion and water -heat carbonized iron, and return high nitrogen -containing liquid -phase products to form bird manure stones with magnesium sources and sludge as high -quality fertilizers.

Benefits of technology

The resource utilization of sludge and iron tail mines has been realized, the process is simplified, the adsorption capacity of adsorption agent is improved, the waste of resources is avoided, and the treatment of high nitrogen -containing products is solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118831562B_ABST
    Figure CN118831562B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of environmental engineering and solid waste resource utilization, and is particularly related to a process for preparing an efficient adsorbent for collaborative phosphorus recovery using sludge / iron tailings. The process includes: (1) the iron tailings are placed in an acid solution for leaching, and solution A is obtained by filtering; (2) the sludge is placed in solution A for impregnation, and solution B is obtained by filtering; (3) the pH of solution B is adjusted to 9-10, and a magnesium source and a nitrogen source are added to the filtrate after filtering and precipitation, and struvite precipitation is obtained after stirring and standing, and struvite and solution C are obtained by filtering; (4) the sludge after impregnation and the precipitation described in step (3) are added to solution C for hydrothermal carbonization reaction, and iron-modified hydrothermal carbon and nitrogen-containing aqueous phase products are obtained after solid-liquid separation; the nitrogen-containing aqueous phase product returns to step (3) as a nitrogen source for recovering struvite. The present invention prepares iron-modified hydrothermal carbon by iron tailings leaching, sludge impregnation, and hydrothermal carbonization process, and the adsorption capacity of hydrothermal carbon is made stronger by the modification of iron. At the same time, the high nitrogen-containing liquid phase product produced by hydrothermal carbonization is returned to the process to form struvite with the magnesium source and phosphorus extracted from the sludge. The struvite can be used directly or indirectly as a high-quality fertilizer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of environmental engineering and solid waste resource utilization, and specifically relates to a process for preparing a high-efficiency adsorbent by utilizing sludge / iron tailings to collaboratively recover phosphorus. Background Art

[0002] Municipal sludge comes from urban domestic sewage treatment plants, with a water content of more than 80%. It contains high levels of organic matter and components such as ammonia and phosphorus required by plants. It also contains pathogens, parasite eggs, heavy metals, organic pollutants and other toxic and harmful pollutants, and has the dual characteristics of "pollution" and "resource". Hydrothermal carbonization is a new type of thermochemical treatment method. When applied to the treatment of high-water-content solid waste such as sludge, it does not require high-energy pre-drying treatment. The water in the sludge is converted into hot compressed water and used as a reaction medium. Under high temperature conditions, organic pollutants in the sludge are degraded, heavy metals are solidified, and hydrothermal carbon materials are produced at the same time, and then environmental functional materials such as adsorbents and soil conditioners are prepared, providing a broad space for the resource utilization of sludge. However, the treatment problem of high-nitrogen liquid products produced by hydrothermal carbonization has become a restrictive factor in the industrial application of sludge hydrothermal carbonization.

[0003] Iron-based materials such as iron and its oxides have the advantages of high surface charge, strong adsorption capacity and easy separation. Iron-modified hydrothermal carbon materials can combine the excellent properties of both hydrothermal carbon and iron-based materials to expand the application of hydrothermal carbon materials in environmental remediation. Iron tailings are the waste left after iron ore is crushed and ground and then subjected to magnetic separation, flotation and other processes. It is the largest bulk solid waste in my country. Using iron tailings as the iron source for iron-modified hydrothermal carbon materials can realize the resource utilization of sludge and iron tailings.

[0004] Prior art, "A sludge-based biochar adsorption material and its preparation method and application" (application publication number CN117960116A), the invention provides a method for preparing biochar adsorption material by carbonization and amination using modified municipal sludge, increasing the metal load and amination degree of the adsorption material, and improving the SO 2 However, the carbonization condition needs to maintain an inert atmosphere, the operation is cumbersome, and more materials and reagents are required, which has certain limitations.

[0005] Prior art, "A method for efficiently recovering phosphorus from municipal sludge" (application publication number CN116621419A), provides a method for recovering phosphorus by adsorbing and desorbing the leachate after acid leaching of the solid phase product of sludge hydrothermal liquefaction, thereby improving the phosphorus recovery rate. However, the process is complicated and involves the adsorption and desorption of phosphorus using activated alumina. In addition, how to deal with the large amount of liquid phase products produced by hydrothermal liquefaction in practical applications is also a problem that needs to be solved. Summary of the invention

[0006] Based on the above content, the purpose of the present invention is to provide a process for preparing an efficient adsorbent using sludge / iron tailings to synergistically recover phosphorus. Iron-modified hydrothermal carbon is prepared by leaching iron tailings, impregnating sludge, and hydrothermal carbonization, and the adsorption capacity of hydrothermal carbon is enhanced by the modification of iron. At the same time, the high nitrogen-containing liquid phase product produced by hydrothermal carbonization is returned to the process to form struvite with the magnesium source and phosphorus extracted from the sludge, and the struvite can be used directly or indirectly as a high-quality fertilizer.

[0007] The purpose of the present invention can be achieved through the following technical solutions:

[0008] The first aspect of the present invention relates to a process for preparing a high-efficiency adsorbent for collaborative phosphorus recovery using sludge / iron tailings, comprising the following steps:

[0009] (1) leaching the iron tailings in an acid solution and filtering to obtain a solution A;

[0010] (2) Immersing the sludge in solution A and filtering to obtain solution B;

[0011] (3) adjusting the pH of solution B to 9-10, filtering the precipitate, adding a magnesium source and a nitrogen source to the filtrate, respectively, stirring and standing to obtain a struvite precipitate, and filtering to obtain the struvite and solution C;

[0012] (4) adding the impregnated sludge and the precipitate of step (3) to solution C for hydrothermal carbonization reaction, and obtaining iron-modified hydrothermal carbon and nitrogen-containing aqueous phase product after solid-liquid separation; the nitrogen-containing aqueous phase product is returned to step (3) as a nitrogen source for recovering struvite.

[0013] Preferably, in step (1), the iron tailings are waste generated after iron ore is subjected to a beneficiation process to select iron concentrate, and have a particle size of 0.1-0.2 mm and an iron content of ≥15%.

[0014] Preferably, the solute of the acid solution in step (1) is one or more of sulfuric acid, citric acid, hydrochloric acid, and acetic acid, and the solvent is deionized water with a concentration of 0.5-1 mol / L.

[0015] Preferably, in step (1), the leaching time is 4-6 h, the temperature is 20-30° C., the volume ratio of the iron tailings mass to the acid solution is 1 g:10 mL, and the iron content of the solution A is ≥10 g / L.

[0016] Preferably, the sludge in step (2) is municipal sludge.

[0017] Preferably, in step (2), the immersion time is 4-6 hours, the temperature is 20-30° C., the volume ratio of sludge mass to iron-containing solution A is 1 g:10 mL, and the phosphorus content of solution B is ≥1.5 g / L.

[0018] Preferably, in step (3), the magnesium source is magnesium chloride or magnesium sulfate solution, with a concentration of 0.1 mol / L, and a volume ratio of 1:1 to solution B; the nitrogen-containing solution is ammonium chloride or ammonium sulfate, with a concentration of 0.1 mol / L, and a volume ratio of 1:2 to solution B. The nitrogen-containing solution may preferably be the aqueous phase product obtained in step (4).

[0019] Preferably, in step (4), the reaction temperature of the hydrothermal carbonization reaction is 200° C., and the reaction time is 2-4 h.

[0020] Preferably, the iron loading of the iron-modified hydrothermal carbon after drying is ≥5%, and the carbon can be used as a highly efficient adsorbent for adsorption of organic pollutants such as tetracycline and rhodamine B, and is suitable for water environment remediation and sewage treatment.

[0021] The second aspect of the present invention relates to iron-modified hydrothermal carbon obtained by the above-mentioned process of preparing a high-efficiency adsorbent for coordinated phosphorus recovery using sludge / iron tailings.

[0022] The third aspect of the present invention relates to the application of the above-mentioned process of preparing a high-efficiency adsorbent for coordinated phosphorus recovery using sludge / iron tailings in the recycling and treatment of sludge / iron tailings or the preparation of iron-modified hydrothermal carbon / struvite.

[0023] Beneficial effects of the present invention:

[0024] (1) The raw materials used in the present invention are two kinds of industrial solid wastes, namely iron tailings and sludge, which effectively realize the resource utilization and harmlessness of solid wastes. At the same time, the adsorbent modified by iron has a good adsorption effect. Under certain adsorption conditions, the equilibrium adsorption amount of oxytetracycline, methylene blue, phenol and nitrobenzene by the iron-modified adsorbent can reach 389 mg / g, 237 mg / g, 317 mg / g and 387 mg / g respectively. The present invention provides a new solution for the reduction, resource utilization and harmless treatment of printing and dyeing sludge.

[0025] (2) The process of the present invention is simple, the raw materials are easy to obtain, and the process is controllable and mild. While preparing a high-efficiency iron-containing adsorbent, it also realizes the recovery of phosphorus in the sludge, thus avoiding waste of resources. In addition, the hydrothermal carbonization aqueous phase product can be returned to the process flow as a nitrogen source for phosphorus recovery, thus realizing the recycling of resources and alleviating the problem of the disposal of the hydrothermal carbonization aqueous phase product. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0027] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION

[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] The present invention is further described in detail below through specific embodiments:

[0030] Example 1

[0031] (1) Preparation of iron-containing leaching solution: The iron tailings were mixed with 0.5 mol / L sulfuric acid at a solid-liquid ratio of 1 g:10 mL at 25°C for 4 h, and the iron-containing solution A was obtained by leaching;

[0032] (2) Sludge impregnation: The sludge and the iron-containing solution A were mixed at a solid-liquid ratio of 1 g:10 mL at 25°C for 4 h to obtain impregnated sludge and phosphorus-containing and iron-containing solution B;

[0033] (3) Recovery of struvite: adjusting the pH of phosphorus- and iron-containing solution B to 9, filtering the iron precipitate, and adding 0.1 mol / L magnesium sulfate and ammonium sulfate solutions to the filtrate, wherein the volume ratio of magnesium sulfate solution, ammonium sulfate solution and solution B is 1.5:1.5:1, stirring, standing, filtering, and obtaining struvite precipitate and solution C;

[0034] (4) Preparation of iron-modified biochar by hydrothermal carbonization: Add the iron precipitate produced by the maceration sludge and struvite recovery process to Solution C, place it in a high-pressure reactor for hydrothermal carbonization, set the hydrothermal carbonization temperature to 200 °C, and the reaction time to 3 h. After the reaction, solid-liquid separation is performed to obtain iron-modified hydrothermal carbon and a high-nitrogen aqueous phase product;

[0035] (5) Product adsorption test: 0.025 g of the iron-modified hydrothermal carbon material was weighed into a 250 mL stoppered conical flask containing 100 mL of oxytetracycline solution with an initial concentration of 50 mg / L. The conical flask was placed in a constant temperature oscillator at 25 °C and 180 r / min. -1 Under the conditions, the mixture was oscillated in a closed manner until adsorption equilibrium was reached. After the adsorption was completed, the mixed solution was filtered through a 0.45 μm water filter membrane. The residual concentration of oxytetracycline was determined using a UV-visible spectrophotometer.

[0036] The equilibrium adsorption capacity q is calculated using the following formula: e .

[0037]

[0038] In the formula, C 0 and C e represent the initial concentration and equilibrium concentration (mg·L -1 ); V represents the volume of the solution (L); m represents the dosage of the iron-modified hydrothermal carbon (g). The results are shown in Table 1.

[0039] Table 1 Example 1 Oxytetracycline adsorption results

[0040]

[0041] Example 2

[0042] (1) Preparation of iron-containing leaching solution: same as in Example 1;

[0043] (2) Sludge impregnation: same as in Example 1;

[0044] (3) Struvite recovery: Same as Example 1, except that the nitrogen source is a high nitrogen-containing aqueous phase product generated by hydrothermal carbonization;

[0045] (4) Preparation of iron-modified biochar by hydrothermal carbonization: Same as Example 1.

[0046] (5) Product adsorption test: 0.025 g of the iron-modified hydrothermal carbon material was weighed into a 250 mL stoppered conical flask containing 100 mL of oxytetracycline solution with an initial concentration of 100 mg / L, and the conical flask was placed in a constant temperature oscillator. Other conditions were the same as those in Example 1. The results are shown in Table 2.

[0047] Table 2 Example 2 Oxytetracycline adsorption results

[0048]

[0049] Example 3

[0050] (1) Preparation of iron-containing leaching solution: The iron tailings were mixed with 0.8 mol / L hydrochloric acid at a solid-liquid ratio of 1 g:10 mL at 25°C for 4 h to obtain an iron-containing solution A;

[0051] (2) Sludge impregnation: The sludge and the iron-containing solution A were mixed at a solid-liquid ratio of 1 g:10 mL at 25°C for 4 h to obtain impregnated sludge and phosphorus-containing and iron-containing solution B;

[0052] (3) Recovery of struvite: adjusting the pH of phosphorus- and iron-containing solution B to 9, filtering the iron precipitate, and adding 0.1 mol / L magnesium chloride and ammonium chloride solutions to the filtrate, wherein the volume ratio of the magnesium chloride solution, the ammonium chloride solution, and the solution B is 1.5:1.5:1, stirring, standing, and filtering to obtain struvite precipitate and solution C;

[0053] (4) Preparation of iron-modified biochar by hydrothermal carbonization: Add the iron precipitate produced by the maceration sludge and struvite recovery process to Solution C, place it in a high-pressure reactor for hydrothermal carbonization, set the hydrothermal carbonization temperature to 200 °C, and the reaction time to 4 h. After the reaction, solid-liquid separation is performed to obtain iron-modified hydrothermal carbon and a high-nitrogen aqueous phase product;

[0054] (5) Product adsorption test: 0.025 g of iron-modified biochar material was weighed into a 250 mL stoppered conical flask containing 100 mL of methylene blue solution with an initial concentration of 60 mg / L. The conical flask was placed in a constant temperature oscillator at 25 °C and 180 r / min. -1 Under the conditions, the mixture was oscillated in a closed manner until adsorption equilibrium was reached. After the adsorption was completed, the mixed solution was filtered through a 0.45 μm water filter membrane. The residual concentration of phenol was determined using a UV-visible spectrophotometer. The results are shown in Table 3.

[0055] Table 3 Example 3 Methylene blue adsorption results

[0056]

[0057] Example 4

[0058] (1) Preparation of iron-containing leaching solution: The iron tailings were mixed with 1 mol / L citric acid at a solid-liquid ratio of 1 g:10 mL at 25°C for 4 h, and the iron-containing solution A was obtained by leaching;

[0059] (2) Sludge impregnation: The sludge and the iron-containing solution A were mixed at a solid-liquid ratio of 1 g:10 mL at 25°C for 4 h to obtain impregnated sludge and phosphorus-containing and iron-containing solution B;

[0060] (3) Recovery of struvite: adjusting the pH of phosphorus- and iron-containing solution B to 10, filtering the iron precipitate, and adding 0.1 mol / L magnesium sulfate and ammonium sulfate solutions to the filtrate, wherein the volume ratio of magnesium sulfate solution, ammonium sulfate solution and solution B is 1.5:1.5:1, stirring, standing, filtering, and obtaining struvite precipitate and solution C;

[0061] (4) Preparation of iron-modified biochar by hydrothermal carbonization: Add the iron precipitate produced by the maceration sludge and struvite recovery process to Solution C, place it in a high-pressure reactor for hydrothermal carbonization, set the hydrothermal carbonization temperature to 200 °C, and the reaction time to 3 h. After the reaction, solid-liquid separation is performed to obtain iron-modified hydrothermal carbon and a high-nitrogen aqueous phase product;

[0062] (5) Product adsorption test: 0.025 g of the iron-modified hydrothermal carbon material was weighed into a 250 mL stoppered conical flask containing 100 mL of a phenol solution with an initial concentration of 80 mg / L. The conical flask was placed in a constant temperature oscillator at 25 °C and 180 r / min. -1Under the conditions, the mixture was oscillated in a closed manner until adsorption equilibrium was reached. After the adsorption was completed, the mixed solution was filtered through a 0.45 μm water filter membrane. The residual concentration of phenol was determined using a UV-visible spectrophotometer. The results are shown in 4.

[0063] Table 4 Example 4 Phenol adsorption results

[0064]

[0065] Example 5

[0066] (1) Preparation of iron-containing leaching solution: same as in Example 4;

[0067] (2) Sludge impregnation: same as in Example 4;

[0068] (3) Struvite recovery: Same as Example 4, except that the nitrogen source is a high nitrogen-containing aqueous phase product generated by hydrothermal carbonization;

[0069] (4) Preparation of iron-modified biochar by hydrothermal carbonization: same as in Example 4;

[0070] (4) Product adsorption test: Weigh 0.025 g of the modified bentonite-hydrothermal carbon composite adsorption material into a 250 mL stoppered conical flask filled with 100 mL of nitrobenzene solution with an initial concentration of 100 mg / L. Place the conical flask in a constant temperature oscillator at 25 °C and 180 r / min. -1 Under the conditions, the mixture was oscillated in a closed manner until adsorption equilibrium was reached. After the adsorption was completed, the mixed solution was filtered through a 0.45 μm water filter membrane. The residual concentration of nitrobenzene was determined using a UV-visible spectrophotometer. The results are shown in Table 5.

[0071] Table 5 Example 3 p-nitrobenzene adsorption results

[0072]

[0073] It should be additionally explained that although iron tailings are used as raw materials in the above embodiments, those skilled in the art should know that other iron-containing waste materials or minerals (with iron content reaching a certain level, for example, within the range specified in the embodiments or invention content of this application) can also be used in the technical solution of this application and achieve the expected effect.

[0074] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0075] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.

Claims

1. A process for preparing a high-efficiency adsorbent for coordinated phosphorus recovery using sludge / iron tailings, characterized in that: The following steps are involved: (1) leaching the iron tailings in an acid solution and filtering to obtain a solution A; (2) Immersing the sludge in solution A and filtering to obtain solution B; (3) adjusting the pH of solution B to 9-10, filtering the iron precipitate, adding a magnesium source and a nitrogen source to the filtrate, respectively, stirring and standing to obtain a struvite precipitate, and filtering to obtain the struvite and solution C; (4) adding the impregnated sludge and the iron precipitate produced in the struvite recovery step to solution C for hydrothermal carbonization reaction, and obtaining iron-modified hydrothermal carbon and nitrogen-containing aqueous phase products after solid-liquid separation; the nitrogen-containing aqueous phase product is returned to step (3) as a nitrogen source for recovering struvite.

2. The process for preparing a high-efficiency adsorbent for coordinated phosphorus recovery using sludge / iron tailings according to claim 1, characterized in that: In the step (1), the iron tailings are waste generated during the process of extracting iron concentrate from iron ore through a beneficiation process.

3. The process for preparing a high-efficiency adsorbent for coordinated phosphorus recovery using sludge / iron tailings according to claim 1, characterized in that: The solute of the acid solution in step (1) is one or more of sulfuric acid, citric acid, hydrochloric acid and acetic acid.

4. The process for preparing a high-efficiency adsorbent for coordinated phosphorus recovery using sludge / iron tailings according to claim 1, characterized in that: In the step (1), the leaching time is 4-6 hours, the temperature is 20-30° C., and the ratio of the mass of the iron tailings to the volume of the acid solution is 1 g:10 mL.

5. The process for preparing a high-efficiency adsorbent for coordinated phosphorus recovery using sludge / iron tailings according to claim 1, characterized in that: The sludge in step (2) is municipal sludge.

6. The process for preparing a high-efficiency adsorbent for coordinated phosphorus recovery using sludge / iron tailings according to claim 1, characterized in that: In the step (2), the immersion time is 4-6 hours, the temperature is 20-30° C., and the volume ratio of sludge mass to solution A is 1 g:10 mL.

7. The process for preparing a high-efficiency adsorbent for coordinated phosphorus recovery using sludge / iron tailings according to claim 1, characterized in that: In the step (3), the magnesium source is magnesium chloride and / or magnesium sulfate.

8. The process for preparing a high-efficiency adsorbent for coordinated phosphorus recovery using sludge / iron tailings according to claim 1, characterized in that: In the step (3), the nitrogen source is ammonium chloride and / or ammonium sulfate.

9. Iron-modified hydrothermal carbon obtained by the process for preparing a high-efficiency adsorbent for coordinated phosphorus recovery using sludge / iron tailings as described in any one of claims 1 to 8.

10. Use of the process for preparing a high-efficiency adsorbent for coordinated phosphorus recovery using sludge / iron tailings as claimed in any one of claims 1 to 8 in recycling sludge / iron tailings or preparing iron-modified hydrothermal carbon / struvite.

Citation Information

Patent Citations

  • Method for efficiently recovering phosphorus from municipal sludge

    CN116621419A

  • Sludge-based biochar adsorption material as well as preparation method and application thereof

    CN117960116A

  • Surplus sludge loaded iron tailing modified adsorbent and method for preparing same

    CN109126411A

  • Magnetic biochar adsorption material based on sulfate reduction sludge as well as preparation method and application thereof

    CN111389363A